TRESK alleviates trigeminal neuralgia induced by infraorbital nerve chronic constriction injury in rats. (October 2019) - Li, Yuanyuan; Jiao, Hena; Ren, Wenan; Ren, Fei
Trigeminal neuralgia commonly results in pain behaviors and cognitive impairment. Convincing evidence suggests that TWIK-related spinal cord K + (TRESK) exerts antinociceptive and neuroprotective effects. However, its possible potentials in trigeminal neuralgia remain unclear. Trigeminal neuralgia model was established in rats by generating an infraorbital nerve chronic constriction injury, and rats received intrathecal injections of TRESK-overexpressing lentivirus and siRNA expression vector-targeted against TRESK (si-TRESK) into the trigeminal ganglions. Mechanical allodynia was evaluated by mechanical withdrawal threshold. Cognitive capacity was tested using Morris water maze. The TRESK expression was determined by quantitative real-time polymerase chain reaction and Western blotting. Results showed that the mRNA and protein levels of TRESK were significantly downregulated in trigeminal ganglions in injured rats. Intrathecal treatment with TRESK reduced mechanical allodynia and relieved learning and memory deficits in trigeminal neuralgia rats, while si-TRESK injection caused neuropathic pain and cognitive deficits. In summary, the present study concluded that TRESK ameliorated pain-associated behaviors and cognitive deficits, which was useful as an alternative approach in management of trigeminal neuralgia.